Electron capture cross sections by different atoms based on the perturbation theory - Shalenov, E.O.; Seisembayeva, M.; Dzhumagulova, K.N. (Recent Contributions to Physics, 2019)
In this work the results of numerical calculation of the electron capture radius in partially ionized plasma are presented. The effective interaction potential was chosen as the electron-atom interaction, which takes into account the screening effect at large distances and the diffraction effect on small distances. The results on the electron capture radius for different chemical elements were obtained based on the perturbation theory. Also, on the basis of the effective interaction potential of an electron with an atom of a nonideal semiclassical plasma, the capture time and the differential capture cross section for different chemical elements are investigated. The results showed that for large values of polarizability coefficient the electron capture radius increases. On the basis of perturbation theory the interaction time between the electron and other atoms was calculated. Studies have shown that with increasing polarizability coefficient the differential capture cross section rises. For this goal the Bohr–Lindhard method has been applied to obtain the electron capture cross section.